1998
DOI: 10.1002/etc.5620171005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aroclor 1248 concentration on the rate and extent of polychlorinated biphenyl dechlorination

Abstract: Abstract-Dechlorination kinetics of polychlorinated biphenyls (PCBs) were investigated in Aroclor 1248-spiked sediments at 16 concentrations ranging from 0 to 200 ppm using sediment microorganisms from the Reynolds site in the St. Lawrence River, New York, USA, over a 58-week incubation period. The time course of dechlorination, measured as the total Cl per biphenyl, consisted of an initial lag phase followed by rapid dechlorination and then a plateau that represented an apparent endpoint of dechlorination. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
65
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(84 citation statements)
references
References 30 publications
(46 reference statements)
18
65
1
Order By: Relevance
“…Sediment slurries in serum vials were autoclaved and then amended with each of the non-PCB HACs (3-, 2,3-, 2,4-, 2,5-, 2,3,5-and 2,4,6-chlorobenzoate; 2,3-, 3,4-, 2,5-, 2,3,6-and penta-chlorophenol ; and 1,2-, 1,2,3-, 1,2,4-and penta-chlorobenzene) in acetone stock solutions (0.5%, v/ v) to yield a ¢nal concentration of 200 Wg (g sediment) 31 . To obtain an inoculum of natural sediment populations, 10 g of the Reynolds site sediments was ¢rst made into slurries in 100 ml of sterilized and reduced synthetic mineral medium, and then stirred for 1 h. After allowing these slurries to settle for 20 min, the supernatant was used as the inoculum.…”
Section: Sediment Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Sediment slurries in serum vials were autoclaved and then amended with each of the non-PCB HACs (3-, 2,3-, 2,4-, 2,5-, 2,3,5-and 2,4,6-chlorobenzoate; 2,3-, 3,4-, 2,5-, 2,3,6-and penta-chlorophenol ; and 1,2-, 1,2,3-, 1,2,4-and penta-chlorobenzene) in acetone stock solutions (0.5%, v/ v) to yield a ¢nal concentration of 200 Wg (g sediment) 31 . To obtain an inoculum of natural sediment populations, 10 g of the Reynolds site sediments was ¢rst made into slurries in 100 ml of sterilized and reduced synthetic mineral medium, and then stirred for 1 h. After allowing these slurries to settle for 20 min, the supernatant was used as the inoculum.…”
Section: Sediment Preparationmentioning
confidence: 99%
“…For laboratory studies, PCB-contaminated sediments were prepared in serum vials by spiking PCB-free sediments with Aroclor 1248 in hexane to yield a concentration of 300 Wg (g sediment) 31 (dry weight basis). The hexane was removed by evaporation.…”
Section: Sediment Preparationmentioning
confidence: 99%
“…Rates of biotransformation are generally directly proportional to solution concentrations rather than total concentrations in sediment (Zwiemik et al 1999), though Sokol et al (1998) found that above concentrations of35 to 45 mg/kg, the dechlorination rate of Aroclor 1248-spiked St. Lawrence River sediments was proportional to concentration in sediment. Because solution concentrations for most congeners are in the low nanogram per liter concentration, transformation rates can be very low.…”
Section: Biotransformation Mechanismsmentioning
confidence: 99%
“…In this case, rates would be slow and difficult to measure, but perhaps significant over multi-year periods. Similarly, Sokol et al (1998) cite studies where dechlorination occurred at PCB concentrations as low as 10 mg/kg sediment and possibly in the ppb range, with bioavailability suggested as the explanation for different thresholds at different sites. PCB dechlorination at Lake Hartwell, SC, apparently occurs at sediment concentrations much lower than 50 mg/kg (Magar et al 2005b).…”
Section: Biotransformation Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation